Renaissance - Volckman, Christian; Craig, Daniel, 1968-; Patrick Floersheim; Catherine McCormack; Laura Blanc; Romola Garai (Miramax USA, 2006)
Paris, 2042: a dark Rotoscope world of shadows and right angles. Ilona Tasuiev, a brilliant young scientist, is kidnapped, and her employer, Avalon, a major health and beauty corporation, wants her found. Karas, a jaded police captain, is assigned to find her, fast. He seeks help from her sister, Bislane, and they are soon uncovering identify theft, missing files, and hints that something back in 2006 may explain what's going on. Ilona's mentor, Avalon's vice president, a Japanese researcher, an underworld boss, and Bislane's drug connection all figure in the mix. So does an attraction between Karas and Bislane. What's behind the kidnapping? Who's the victim?
Paris 2054. Live forever or die trying.
Languages : English, Turkish Subtitle : Turkish
Keywords: Action -- Animation -- Adventure; Fantasy -- Drama -- SciFi